Islam as a basis for civilization thought and development - Abdullah Ahmad Badawi (Penerbit Universiti Kebangsaan Malaysia, 2017)
This article discuss a brief meaning of civilization and development in Islam, how Islamic civilization and development have impacted the world community particularly in intellectual fields, the significance of Islamic thought on civilization and development in the midst of contemporary scientific and technological developments before linking all these topics back to the basis for civilizational thought and development set forth by al-Quran and dwell further on the cooperative effort, particularly by Malaysian and Japanese scholars, on understanding Islamic thought in relation to civilization and development at international level.